Statement on the safety of synthetic l‐ergothioneine as a novel food – supplementary dietary exposure and safety assessment for infants and young children, pregnant and breastfeeding women. (13th November 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to provide a supplementary dietary exposure and safety assessment of syntheticl ‐ergothioneine for those groups of the population which had been excluded by the applicant in the original application, i.e. infants and young children (i.e. toddlers), pregnant and breastfeeding women. Thus, intake estimates were calculated for these population groups and the following maximum anticipated daily intakes ofl ‐ergothioneine from the NF, in addition to the background diet, were calculated: 2.82 mg/kg body weight (bw) per day for infants, 3.39 mg/kg bw per day for toddlers and 1.31 mg/kg bw per day for adults including pregnant and breastfeeding women. The Panel considers that based on the overall toxicological data the no‐observed‐adverse‐effect level (NOAEL) of 800 mg/kg bw per day as established in the original assessment also pertains to pregnant and breastfeeding women as well as to young children (i.e. toddlers) and infants. The corresponding margins of exposure (i.e. the ratio between the NOAEL and the maximum anticipated daily intakes) are 284 for infants, 236 for young children and 610 for pregnant and breastfeeding women. These margins of exposure are considered sufficient. The Panel concludes that the novel food, syntheticl ‐ergothioneine, is safe under the proposed uses and use levels for infants, young children (i.e. toddlers) and pregnant and breastfeeding women.